GENDER: INTEGRATING CRIMES AGAINST WOMEN INTO INTERNATIONAL CRIMINAL LAW - Mohammad Irfan (UNISSULA, 2018)
The author identifies the major goals and achievements in the area of recognizing women as full subjects of human rights and eliminating impunity for gender crimes, highlighting the role of non-governmental organizations (